BIRDS POPULATION AND THEIR NEST CHARACTERISTICS IN CITY TERRITORIES (ON EXAMPLE OF KISLOVODSK CITY) - V. A. TELPOV (Юг России: экология, развитие)
In this article the influence of human impact on a specific variety of birds, character of their stay and feature of placing their nests in city territory is analyzed.